Bridge of Clay - Zusak, Markus (New York Alfred A. Knopf, 2018)
Upon their father's return, the five Dunbar boys, who have raised themselves since their mother's death, begin to learn family secrets, including that of fourth brother Clay, who will build a bridge for complex reasons, including his own redemption.
Keywords: Brothers -- Juvenile fiction; Abandoned children -- Juvenile fiction; Secrecy -- Juvenile fiction; Families -- Juvenile fiction; Bridges -- Juvenile fiction -- Design and construction; Brothers -- Fiction; Abandoned children -- Fiction; Secrets -- Fiction; Family life -- Fiction; Bridges -- Fiction -- Design and construction